MULTICULTURALISM OF VISUAL ART EDUCATION CURRICULUM IN SECONDARY SCHOOL TOWARDS ART TEACHERS - Azwady Mustapha; Mohamad Quzami An-Nuur Ahmad Radzi; Zainudin Md. Nor; Rosha Mohamed, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This purpose of this research is to explore multiculturalism in the teaching of secondary school visual art in the district of Temerloh, Pahang, Malaysia. Multiculturalism is integral, as a foundation to promote national intergrity. This research adopted the qualitative case study approach. The methods used in this research were document analysis and interview. A total of three document policies were collected and analysed. The interview was conducted using a semi-structured interview towards six visual art teachers in secondary schools and a Head Unit of the Visual Art Education from the Ministry of Education Curriculum Development Division. The research indicated that the visual art teaching has the elements of multiculturalism. The government policy also urged that the aspect of multiculturalism is integrated in the education. Nevertheless, the integration did not happen consciously. The data obtained showed that there were positive values among the school citizens. Teachers' attitudes, especially the beliefs and values were encouraging even though the knowledge to the integration of multiculturalism is still low. In order to attain a higher level of understanding, visual art teachers have to be exposed to workshop, courses and seminars that are appropriate. The Visual Art curriculum needs to be reviewed to reflect multiculturalism a clearer manner.